1982
DOI: 10.1021/jf00110a030
|View full text |Cite
|
Sign up to set email alerts
|

Free, esterified, and insoluble-bound phenolic acids. 3. Composition of phenolic acids in cereal and potato flours

Abstract: Plant Materials. The samples analyzed for phenolic composition included Neepawa wheat, Neepawa wheat flour, Harmon oats, yellow dent com, long grain brown rice, and Netted Gem potatoes.The seed samples were mature, sound, and, except for rice, had been harvested about 2 months previously.The cereals, after dehulling in the case of oats, were debranned by roller milling or pearling and ground into a fine flour. The potatoes were peeled, sliced, freeze-dried, and ground.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
279
4
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(307 citation statements)
references
References 2 publications
20
279
4
2
Order By: Relevance
“…Their potent antioxidant activity is due to the redox properties of their hydroxyl groups (Materska and Perucka 2005;Rice-Evans et al 1996;Rice-Evans et al 1997). Phenolics are present in plant in both free and bound forms; bound phenolics mainly in the form of β-glycosides, may survive human stomach and small intestine digestion and reach the colon intact, where they are released and exert their bioactivity (Sosulski et al 1982); while free phenolics are more readily absorbed and thus, exert beneficial bioactivities in early digestion; however, the significance of bound phytochemicals to human health is not clear Sun et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Their potent antioxidant activity is due to the redox properties of their hydroxyl groups (Materska and Perucka 2005;Rice-Evans et al 1996;Rice-Evans et al 1997). Phenolics are present in plant in both free and bound forms; bound phenolics mainly in the form of β-glycosides, may survive human stomach and small intestine digestion and reach the colon intact, where they are released and exert their bioactivity (Sosulski et al 1982); while free phenolics are more readily absorbed and thus, exert beneficial bioactivities in early digestion; however, the significance of bound phytochemicals to human health is not clear Sun et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Free phenolic acids are found in outer layer of the pericarp whereas bound phenolic acids are ester-linked to cell walls and require acid, base or enzymatic hydrolysis to release them from the cell matrix [47]. Durkee and Thivierge [48] reported low levels of free ferulic, vanillic, sinapic and p-hydroxybenzoic acids in 70% ethanol solid liquid extracts from oat grains.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…The first quantitative data on the various phenolic acids in oats, other than ferulic acid, was reported by Sosulski et al [47]. The authors extracted phenolic acids from oat flour and separated them into three fractions: free, soluble esters and insoluble bound.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Ferulic and p-coumaric acid are the main phenolic acids found in monocotyledonous plants with ferulic acid constituting more than 90% of total phenolic acid in wheat flour [13]. Comparisons between a black point susceptible and tolerant durum wheat variety has found that the susceptible variety contained higher levels of ferulic acid and increased activity of phenylalanine ammonia lyase (PAL), an enzyme involved in phenolic acid biosynthesis [14].…”
Section: Introductionmentioning
confidence: 99%